Evaluation of sperm counting accuracy on computer-assisted sperm analysis with GoldCyto® slides and glass slides - Akal, Eser (Frontiers in Veterinary Science, 2023)
Worldwide, various counting chambers and computer-assisted sperm analysis (CASA) devices are in use. The semen's concentration can vary depending on the depth of the counting chamber and how it is loaded. The study's objectives were to analyze the effects of various counting chambers on semen concentration results using a GoldCyto ® slide and a glass slide in the CASA system and to ascertain the precision of concentration measurements made using glass slides on CASA. The study's control group was composed of samples with known concentrations (72-80 million sperm/ml) as determined by a spectrophotometer. A total of 21 frozen straws from the same bull of the same date were thawed at 37 °C for 30 seconds and loaded into two different sperm-counting chambers (GoldCyto ® slide and glass slide). The sample semen placed in the sperm counting chambers was 5 µl and the same value was entered in the CASA software as 5 µl. Measurements were done and evaluated in 5 different areas. According to the data we obtained, using the glass slide were statistically lower than the spectrophotometer (p<0.001). GoldCyto ® slide results were consistent with spectrophotometer results. Consequently, measurements with GoldCyto ® slides in the CASA had consistent results, while measurements with glass slides were inconsistent. It was concluded that GoldCyto ® slides are more suitable than glass slides in the concentration examinations of semen. Therefore, more study is needed to optimize the use of glass slides.